Two Heads Hidra: Ricoeurian Configuration and Impure Narrator in a Narrative of HC - FMUSP - Carelli, Fabiana; Funchal Lens, Andrea; Cabral Carvalho Alcântara De Oliveira, Amanda; Dos Santos, Ariadne Catarine; Dos Reis, Mariluz; Pompilio, Carlos Eduardo (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2013)
This article aims to analyze how it is configured the narrative of life of a patient of the General and Didactic Clinic of the University of São Paulo School of Medicine, in a consultation with the resident who attends her, and how that narrative is reconfigured by the same resident, both in the conversation with her assistant and at the resumption of the consultation with the patient. The analysis is based on the concepts of prefiguration, configuration and refiguration established by Paul Ricoeur in his book Time and Narrative (2010); narrator and narrative point of view, in Arrigucci Jr. (1998) and Friedman (2002); and the cultural aspects of the comic genre, in Aristotle (s/d), Darnton (1996), Bakhtin (1999) and Baudelaire (2002). This paper aims to propose some analytical and theoretical grounds for the concept of a “cleaved’ or “impure” narrator in the context of the relations between narrative and medicine.